WNT4 promotes the symmetric fission of crypt in radiation-induced intestinal epithelial regeneration - Jingyang Cheng; Haiyong Wu; Yanmei Cui (Cellular & Molecular Biology Letters)
Abstract Background Radiotherapy for pelvic malignant tumors inevitably causes intestinal tissue damage. The regeneration of intestinal epithelium after radiation injury relies mainly on crypt fission. However, little is known about the regulatory mechanisms of crypt fission events. Methods The effects of WNT4 on crypt regeneration and the symmetry of crypt fission were examined using a mouse small intestinal organoid culture model. Three-dimensional (3D) reconstructed images of organoids were applied to assess the symmetry of crypt fission and Paneth cell localization upon manipulation of WNT4 expression. The effect of WNT4 on the expression of β-catenin target genes was analyzed by real-time quantitative polymerase chain reaction (RT-qPCR). The in vivo effect of WNT4 overexpression mediated by adeno-associated virus (AAV) on symmetric fission of crypt was investigated using a radiation-injured mouse model. Results WNT4 has a special function of promoting symmetric fission of small intestinal crypts, although it inhibits budding, stemness, and cell proliferation on organoids. WNT4 promotes the correct localization of Paneth cells in the crypt base by regulating the expression of EphB3, thereby promoting the symmetric fission of small intestinal crypts. WNT4 negatively regulates the canonical WNT/β-catenin signaling pathway, and it promotes symmetric crypt fission in a ROR2 receptor-dependent manner. Moreover, in patients and animal models of radiation-induced intestinal injury, we found that the regenerated crypts are irregular in size and shape, Paneth cells are mislocalized, and the expression of WNT4 is decreased while EphB3 is increased. Importantly, restoration of WNT4 expression mediated by AAV effectively promotes symmetric crypt fission and thus improves the regularity of regenerating crypts in mice with radiation-induced injury. Conclusions Our study highlights the critical role of WNT4 in the regulation of crypt fission and provides WNT4 as a potential therapeutic target for radiation enteritis. Graphical Abstract